2021
DOI: 10.3390/antibiotics10111323
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterial DNA Methyltransferase HsdM Decreases Intrinsic Isoniazid Susceptibility

Abstract: Tuberculosis, caused by the pathogen Mycobacterium tuberculosis, is a serious infectious disease worldwide. Multidrug-resistant TB (MDR-TB) remains a global problem, and the understanding of this resistance is incomplete. Studies suggested that DNA methylation promotes bacterial adaptability to antibiotic treatment, but the role of mycobacterial HsdM in drug susceptibility has not been explored. Here, we constructed an inactivated Mycobacterium bovis (BCG) strain, ΔhsdM. ΔhsdM shows growth advantages over wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…In a previous study, the mutated mycobacterial strain, mc 2 51, evolved into an M. tuberculosis -like strain that presented slow growth and improved growth fitness under stress ( Li et al, 2014b ), which H 2 O 2 resistance in mycobacteria linked to virulence. Previous studies including ours have associated isoniazid (INH) with H 2 O 2 resistance ( Timmins and Deretic, 2006 ; Hu et al, 2021 ). The MIC of isoniazid (INH) for mc 2 51 was dramatically reduced to ∼1% of the MIC for mc 2 155 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous study, the mutated mycobacterial strain, mc 2 51, evolved into an M. tuberculosis -like strain that presented slow growth and improved growth fitness under stress ( Li et al, 2014b ), which H 2 O 2 resistance in mycobacteria linked to virulence. Previous studies including ours have associated isoniazid (INH) with H 2 O 2 resistance ( Timmins and Deretic, 2006 ; Hu et al, 2021 ). The MIC of isoniazid (INH) for mc 2 51 was dramatically reduced to ∼1% of the MIC for mc 2 155 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 89%
“…Clinical investigation has shown that cells from TB patients produce less ROS than those of healthy individuals ( Jaswal et al, 1992 ; Kumar et al, 1995 ). In addition, ROS can also be associated with the treatment of TB ( Piccaro et al, 2014 ; Hu et al, 2021 ). To avoid ROS attack, an evolved detoxified system is essential for M. tuberculosis survival, persistence, and subsequent reactivation ( Piccaro et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…MamA, MamB, and HsdM are three known DNA MTases coded by M. tb, which target different sequence pattern for N6-adenine methylation (Shell et al, 2013;Zhu et al, 2016). Mycobacterial DNA methyltransferase HSdM regulates transcription and decreases susceptibility to isoniazid (Hu et al, 2021). Rv1988 is a secretory methyltransferase that enters the nucleus of the host and methylates histone H3 at arginine residues, regulating the expression of genes that neutralise reactive oxygen species (Yaseen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The number of hsdM-methylated motifs is almost double in BCG (674) than in clinical XDR-TB isolates 11826 (368). In comparison to their parent strain, the knockout of hsdM in BCG did not reveal a growth difference, while the knockout of hsdM in XDR-TB 11826 showed a drop in growth [ 21 ]. There were also some reports on the HsdM homolog in other bacterial species, such as in streptococci (e.g., S. pyogenes and S. agalactiae), which might involve bacterial drug resistance and other physiological features such as growth, hypoxia, and UV stress [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%